A review of human carcinogens. Part C: arsenic, metals, fibres and dusts (Lyon, 2012)
"This Volume 100C covers Arsenic, Metals, Fibres, and Dusts, specifically Arsenic and Arsenic Compounds, Beryllium and Beryllium Compounds, Cadmium and Cadmium Compounds, Chromium (VI) Compounds, Nickel and Nickel Compounds, Asbestos (Chrysotile, Amosite, Crocidolite, Tremolite, Actinolite and Anthophyllite), Erionite, Leather Dust, Silica Dust, Crystalline, in the form of Quartz or Cristobalite, and Wood Dust. Because the scope of Volume 100 is so broad, its Monographs are focused on key information. Each Monograph presents a description of a carcinogenic agent and how people are exposed, critical overviews of the epidemiological studies and animal cancer bioassays, and a concise review of the agent's toxicokinetics, plausible mechanisms of carcinogenesis, and potentially susceptible populations, and life-stages. Details of the design and results of individual epidemiological studies and animal cancer bioassays are summarized in tables. Short tables that highlight key results are printed in Volume 100, and more extensive tables that include all studies appear on the Monographs programme website (http://monographs.iarc.fr).